Related but not alike: not all Hemiptera are attracted to yellow - Farnier, Kevin; Dyer, Adrian G.; Steinbauer, Martin J. (Frontiers in Ecology and Evolution, 2014)
Most innate responses to color stimuli lead herbivorous insects to orient to “green” and “yellow” surfaces. Early research showed that aphid orientation to plants is influenced by foliar pigments and leads them to alight on leaves of a specific physiological state regardless of whether or not it is their actual host. In this study, we quantified the color preferences of four psyllids specialized on young to recently expanded leaves of different Eucalyptus hosts presenting distinct between (inter-specific) and within canopy (ontogenic) optical characteristics. Color preferences of Ctenarytaina eucalypti and C. bipartita were similar to those observed in aphids with more frequent selection of yellow and green stimuli, consistent with the coloration of their host leaves. However, attraction of Anoeconeossa bundoorensis and Glycaspis brimblecombei to a red stimulus contrasts strongly with the literature for hemipteran and herbivorous insects generally for which attraction to red is peculiar. Interestingly, both red-attracted species occur on the same host eucalypt, which expresses anthocyanic (red) young leaves. Our experiments demonstrate that these two species are sensitive to long wavelength radiation. Behavioral work and modeling of putative “aphid-like” photoreceptors were conducted to investigate whether achromatic vision mediates perception of “red”. Our results do not provide strong evidence for an intensity-dependant type of attraction. Nevertheless, the current knowledge of photoreceptors in Hemiptera identifies the achromatic as the most likely mechanism for detecting long wavelengths. Thus, our findings highlight the need for physiological work with Psylloidea to dissect the mechanisms responsible for such atypical responses. We discuss the ecological implications of our work in relation to red foliar pigments in expanding leaves of perennial plants which differs greatly from the thoroughly studied aphid-autumnal leaves system involving senescing foliage.